If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3x + 2y) + -7x + -5(2y + -4) = 0 (3x * 4 + 2y * 4) + -7x + -5(2y + -4) = 0 (12x + 8y) + -7x + -5(2y + -4) = 0 Reorder the terms: 12x + 8y + -7x + -5(-4 + 2y) = 0 12x + 8y + -7x + (-4 * -5 + 2y * -5) = 0 12x + 8y + -7x + (20 + -10y) = 0 Reorder the terms: 20 + 12x + -7x + 8y + -10y = 0 Combine like terms: 12x + -7x = 5x 20 + 5x + 8y + -10y = 0 Combine like terms: 8y + -10y = -2y 20 + 5x + -2y = 0 Solving 20 + 5x + -2y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + 5x + -20 + -2y = 0 + -20 Reorder the terms: 20 + -20 + 5x + -2y = 0 + -20 Combine like terms: 20 + -20 = 0 0 + 5x + -2y = 0 + -20 5x + -2y = 0 + -20 Combine like terms: 0 + -20 = -20 5x + -2y = -20 Add '2y' to each side of the equation. 5x + -2y + 2y = -20 + 2y Combine like terms: -2y + 2y = 0 5x + 0 = -20 + 2y 5x = -20 + 2y Divide each side by '5'. x = -4 + 0.4y Simplifying x = -4 + 0.4y
| 224/32= | | 3(-4m-6)=-6(m+3) | | 30*93= | | -38-7k=-8(k+4) | | 32/224 | | -2x-1=-9x-x | | 5/9=1/4x | | 25*79= | | 26x=27x-5 | | 2y^3+3y^2=0 | | 5x+10y=-2 | | 157=-192+h | | 11*38= | | -2z/2 | | 4f-9-3f+10= | | -18=-15-3(6t+5) | | 0(5m)=5m | | -x+3+3x=-19 | | 3=(3+2x)-2(1+3x) | | x-44=90 | | 6-4(x-1)=3x+2(x+5) | | 15*44= | | 12x+6=13x-1 | | 11y+2y= | | -(-40)+m=65 | | 3(y-2)=6y+1-2(-6y-1) | | 9*57= | | 6x=3x+-2+28 | | 95=5(2-y) | | 3000/40-40x= | | 3a+5b=14 | | -5x+2=x+26 |